Great books, honors programs, and hidden origins : the Virginia Plan and the University of Virginia in the liberal arts movement. - Haarlow, William N. (Studies in the history of education (RoutledgeFalmer (Firm)), 2003)
The importance of this book comes from building upon and improving the historical literature on the liberal arts movement in specific, and higher education curricular reform in general.